Analysis and Design of Noise Barrier Based on Analytical Hierarchy Process (AHP) Method - Erlangga Bagaskara; Priyambodo Nur Ardi Nugroho; Denny Dermawan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Noise is one of the potential hazards that must be controlled to prevent occupational diseases. In one office area, the noise level exceeds the limits stipulated in the Ministry of Manpower Regulation No. 5 of 2018. Based on preliminary interviews, the installation of a noise barrier is urgently required. The selection of the type of material and the design of the noise barrier shape was carried out using the Analytical Hierarchy Process (AHP) method. The selection criteria included material, cost, aesthetics, material weight, safety, and ease of installation and maintenance. The determination of height variations was conducted using the Maekawa method. A gypsum board noise barrier with a vertical shape and a height of 1,94 meters was able to reduce the noise level in the office area exposed to 87,83 dBA down to 48,01 dBA, as validated using COMSOL Multiphysics 6.0 software. Unlike previous studies, the difference in validation results lies in the design selection using the AHP method.